FORGIVENESS AS A PATHWAY TO TRAUMA HEALING: A NARRATIVE EXAMINATION OF COLLEEN HOOVER’S REMINDERS OF HIM - Azzahra, Rindiani; Siwi, Purwanto; Rahmawati, Rahmawati (JOURNAL OF LANGUAGE, 2025)
This study examines the role of forgiveness in the trauma healing process as portrayed in Colleen Hoover’s Reminders of Him. Focusing on the main character, Kenna Rowan, it explores how she experiences emotional trauma and how forgiveness facilitates her recovery. Using a qualitative descriptive method with a psychological approach, the analysis applies Worthington’s model of decisional and emotional forgiveness and Enright’s Four-Phase Model of Forgiveness to identify the stages of healing depicted in the narrative. The findings reveal that Kenna exhibits symptoms of psychological trauma, including anxiety, guilt, avoidance, flashbacks, and difficulty maintaining relationships. The study identifies two types of forgiveness—decisional, a conscious choice to forgive, and emotional, a deeper emotional release—and demonstrates how Kenna’s journey reflects the four phases of forgiveness: uncovering, decision, work, and deepening. Through self-reflection, acceptance, and social support, she achieves self-forgiveness and re-establishes connections with her daughter and others. The research concludes that forgiveness is a key factor in emotional recovery and that literature can serve as a valuable medium for understanding psychological healing and personal growth.